2021
DOI: 10.1016/j.nicl.2021.102560
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant brain oscillatory coupling from the primary motor cortex in children with autism spectrum disorders

Abstract: Highlights We measured brain oscillation and oscillatory coupling during motor control in ASD. ASD group showed reduced motor-related gamma increases compared with control group. ASD group showed enhanced pre-movement beta decreases compared with control group. ASD group showed reduced beta-gamma phase-amplitude coupling during motor control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
2
16
0
1
Order By: Relevance
“…In a series of studies with MEG and a game-like motor task An et al (2018 , 2021) investigated the neural responses associated with finger presses in normal and ASD children. These studies showed a decrease in gamma peak activity ( An et al, 2018 ) and decreased beta-gamma ipsilateral PAC activity ( An et al, 2021 ) in M1 of ASD children in comparison with healthy participants. Once again, these modulations of motor gamma oscillations may reflect an unbalance in the excitatory and inhibitory neurotransmission systems.…”
Section: Motor Gamma Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of studies with MEG and a game-like motor task An et al (2018 , 2021) investigated the neural responses associated with finger presses in normal and ASD children. These studies showed a decrease in gamma peak activity ( An et al, 2018 ) and decreased beta-gamma ipsilateral PAC activity ( An et al, 2021 ) in M1 of ASD children in comparison with healthy participants. Once again, these modulations of motor gamma oscillations may reflect an unbalance in the excitatory and inhibitory neurotransmission systems.…”
Section: Motor Gamma Oscillationsmentioning
confidence: 99%
“…This notion converges with the idea of an altered neurotransmission balance in schizophrenia (Gaspar et al, Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by deficits in social communication, restricted interests, and repetitive behaviors (American Psychiatric Association, 2013). In a series of studies with MEG and a game-like motor task An et al (2018An et al ( , 2021 investigated the neural responses associated with finger presses in normal and ASD children. These studies showed a decrease in gamma peak activity (An et al, 2018) and decreased beta-gamma ipsilateral PAC activity (An et al, 2021) in M1 of ASD children in comparison with healthy participants.…”
Section: Neurobiological Mechanisms and Physiopathologymentioning
confidence: 99%
“…More evidence has been provided that patients with motor abnormalities or processing speed slowing displayed attenuated PMBR. For example, Robson et al found aberrant PMBR activity in SCH [44], as well as ASD [47][48][49] and PD [40][41][42]. The evidence suggests that the reduced PMBR activity is characteristic of patients with aberrant psychomotor performance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that poor motor performance in healthy older adults is related to changes in beta oscillations. Importantly, neuropsychiatric studies also revealed that decreased PMBR in PD [40][41][42], SCH [43][44][45], schizotypal personality disorder (SPD) [46] , autism spectrum disorder (ASD) [47][48][49] , re ecting impaired sensorimotor integration in psychiatric disease. In general, these ndings indicated that the aberrant PMBR impacts motor-related activity and advanced sensorimotor integration.…”
Section: Introductionmentioning
confidence: 99%
“…Помимо болезни Альцгеймера, ТГС исследовали у пациентов с психическими заболеваниями: шизофренией [71,72], расстройствами аутистического спектра [73,74], рекуррентной депрессией [75,76], синдромом дефицита внимания с гиперактивностью [77,78]. Наибольшее количество работ по изучению ТГС включали пациентов с шизофренией, хотя ограничением является гетерогенность их методологии.…”
Section: корреляция с когнитивными тестами у здоровыхunclassified